Competitive and synergistic adsorption of mixtures of polar and nonpolar gases in carbonaceous nanopores - Tan, Johnathan Shiliang (2022)
Most adsorption applications involve mixtures, yet accurate predictions of the adsorption of mixtures remain challenging, in part due to the inability to account for the interplay between adsorbate-adsorbate and adsorbate-adsorbent interactions. This study involves a comprehensive Monte Carlo simulation of the adsorption of two groups of mixtures (namely, supercritical and subcritical ones) in carbon nanopores and quantifies Henry's constants, isotherms, energetics, and density distributions in the pores. When interadsorbate interactions are negligible (e.g., in supercritical mixtures such as mixtures of nonpolar gases), adsorbates behave like ideal gases and the adsorption isotherm can be predicted with the ideal adsorbed solution theory (IAST). However, when interadsorbate interactions become significant, IAST fails. This study reveals that (1) in mixtures of polar and nonpolar gases, the stronger intermolecular interaction for the polar constituent leads to synergistic adsorption that causes the nonpolar adsorbate to desorb and (2) for mixtures of polar gases, such as ethanol and water, the adsorbate-adsorbate interactions are so dominant that the unfavorable adsorbate-adsorbent interactions are overcome, such that water adsorbs onto the hydrophobic adsorbent. The competitive and synergistic interactions highlighted here are expected to be valuable in enhancing gas separations.